Inferências filogenéticas de cinco estirpes isoladas de Leptospira de suínos baseados nos genes 16s e secY - Bastos, C. R.; Marulanda, N. D. F.; Jaeger, L. H.; Miranda, V. F. O.; Lilenbaum, W.; Mathias, L. A. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Leptospirosis is a zoonosis responsible for economic and health damage in swine herds. The cultivation and typing of leptospire strains present in one region are still an important subject to bring knowledge for disease control.